The kinetic properties of the α3 rat glycine receptor make it suitable for mediating fast synaptic inhibition. (28th May 2013) - Marabelli, Alessandro; Moroni, Mirko; Lape, Remigijus; Sivilotti, Lucia G.
Key points:   In the adult, most inhibitory transmission mediated by glycine uses channels containing α1 subunits, but both α1 and the related α3 subunit are present in spinal areas that process pain.   We recorded the effect of a range of fixed glycine concentrations on the activity of individual glycine channels expressed in vitro to contain only α3 subunits.   Glycine is very effective in opening α3 channels. At full activation, both α1 and α3 channels are open nearly 100% of the time, but α3 channels need all, or almost all, of the five glycine binding sites to be occupied, whereas α1 channels need only three.   When channels were activated in synaptic‐like conditions (fast, 1 ms, 10 mm glycine pulses), α3 responses decayed more slowly than α1 responses.   This difference is likely to be too small to allow α1‐ and α3‐mediated synaptic responses to be distinguishable on the basis of time course alone. Abstract  Glycine receptors mediate fast synaptic inhibition in spinal cord and brainstem. Two α subunits are present in adult neurones, α1, which forms most of the synaptic glycine receptors, and α3. The physiological role of α3 is not known, despite the fact that α3 expression is concentrated in areas involved in nociceptive processing, such as the superficial dorsal horn. In the present study, we characterized the kinetic properties of rat homomeric α3 glycine receptors heterologously expressed in HEK293 cells. We analysed steady state single channel activity at a range of different glycine concentrations by fitting kinetic schemes and found that α3 channels resemble α1 receptors in their high maximum open probability (99.1% cf. 98% for α1), but differ in that maximum open probability is reached when all five binding sites are occupied by glycine (cf. three out of five sites for α1). α3 activation was best described by kinetic schemes that allow the channel to open also when partially liganded and that contain more than the minimum number of shut states, either as desensitized distal states (Jones and Westbrook scheme) or as pre‐open gating intermediates (flip scheme). We recorded also synaptic‐like α3 currents elicited by the rapid application of 1 ms pulses of high concentration glycine to outside‐out patches. These currents had fast deactivation, with a time constant of decay of 9 ms. Thus, if native synaptic currents can be mediated by α3 glycine receptors, they are likely to be very close in their kinetics to α1‐mediated synaptic events.